2021
DOI: 10.1162/leon_a_02054
|View full text |Cite
|
Sign up to set email alerts
|

Slow Looking at Slow Art: The Work of Pierre Bonnard

Abstract: Slow looking is an increasingly prevalent strategy for enhancing visitor engagement in the gallery, yet there is little research to show why looking at artworks for longer should be beneficial. The curator of a recent exhibition of Pierre Bonnard at the Tate Gallery in London encouraged viewers to look slowly in order to enrich their experience of Bonnard’s paintings. This article explores some of the reasons why Bonnard’s work, in particular, rewards the viewer who spends more time studying it. The authors dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…For example, Cézanne painted objects in the centre of his compositions, these being his main focus of attention, much larger than they appear in the equivalent photographs relative to objects in the visual periphery, as illustrated in Figure 1 (Pepperell & Haertel, 2014). Similarly, Pierre Bonnard's depictions of interiors show centrally fixated objects much larger and peripheral objects diminished in size compared with photographs of the same interiors (Burleigh et al, 2018(Burleigh et al, , 2021Chamberlain & Pepperell, 2020).…”
Section: Spatial Perception In Linear and Natural Perspectivesmentioning
confidence: 96%
“…For example, Cézanne painted objects in the centre of his compositions, these being his main focus of attention, much larger than they appear in the equivalent photographs relative to objects in the visual periphery, as illustrated in Figure 1 (Pepperell & Haertel, 2014). Similarly, Pierre Bonnard's depictions of interiors show centrally fixated objects much larger and peripheral objects diminished in size compared with photographs of the same interiors (Burleigh et al, 2018(Burleigh et al, , 2021Chamberlain & Pepperell, 2020).…”
Section: Spatial Perception In Linear and Natural Perspectivesmentioning
confidence: 96%
“…There is also the possibility that certain categories of art, or even specific features in certain artists' works (Chamberlain & Pepperell, 2021), are better suited for slow viewing. Indeed, there was an array of photographic, representational, and abstract works showcased by each institution for their online slow viewing events, although abstract art was shown more frequently by the hosting educators (Slow Art Day, 2021).…”
Section: Not All Art Is Created Equalmentioning
confidence: 99%
“…de Heem was chosen as the representational artist, and Fernand Léger was chosen as the abstract artist (see Figure 1 for sample representational and abstract works; see https://osf.io/3bajp/ for a link to photographic work). Furthermore, participants also indicated that they preferred a viewing time of 3 min, which is less than traditional in-person slow viewing exercises (Chamberlain & Pepperell, 2021) but considerably more than average unaided viewing times reported within galleries (Carbon, 2017; J. K. Smith & Smith, 2001;L. F. Smith et al, 2017).…”
Section: Viewing Taskmentioning
confidence: 99%
“…There is also the possibility that certain categories of art, or even specific features in certain artists' works (Chamberlain & Pepperell, 2021), are better suited for slow viewing. When it comes to general preferences for art viewing, there is evidence to suggest that non-expert viewers prefer representational art over abstract art (Pihko et al, 2011;Uusitalo et al, 2012), and that representational artworks show greater convergence of evaluation and associations across viewers (Schepman et al, 2015).…”
Section: Is All Art Created Equal For Slow Looking?mentioning
confidence: 99%
“…de Heem was chosen as the representational artist, and Fernand Léger was chosen as the abstract artist (see Figure 1). Furthermore, participants also indicated that they prefer a viewing time of 3 minutes, which is less than traditional in-person slow viewing exercises (Chamberlain & Pepperell, 2021) but considerably more than average unaided viewing times reported within galleries (Carbon, 2017;Smith & Smith, 2001). Lastly, survey respondents also indicated that loss of focus was a major factor, so a pre-viewing focusing exercise was added to the protocol.…”
Section: Pilot Studymentioning
confidence: 99%